2022
DOI: 10.3390/nu14030667
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus Is Associated with Differences in Human Milk Hormone and Cytokine Concentrations in a Fully Breastfeeding United States Cohort

Abstract: It is unclear whether gestational diabetes mellitus (GDM) alters breast milk composition. We prospectively examined associations of GDM status with concentrations of six potentially bioactive elements (glucose, insulin, C-reactive protein (CRP), interleukin-6 (IL-6), leptin, and adiponectin) in human milk. These were measured at both 1 and 3 months postpartum in 189 fully breastfeeding women. Mixed-effects linear regression assessed GDM status-related differences in these milk bioactives, adjusting for demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 61 publications
1
14
1
Order By: Relevance
“…Colostrum and breast milk from GDM mothers present decreased levels of antibodies and less monocyte phagocytic capacity ( 35 ). However, another study showed no difference in the mature milk composition regarding cytokines and hormones comparing healthy to GDM mothers ( 13 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Colostrum and breast milk from GDM mothers present decreased levels of antibodies and less monocyte phagocytic capacity ( 35 ). However, another study showed no difference in the mature milk composition regarding cytokines and hormones comparing healthy to GDM mothers ( 13 ).…”
Section: Discussionmentioning
confidence: 98%
“…Some factors can influence colostrum composition, such as genetics, environment and geographical location, food consumption, lactation stage, and maternal nutritional status and health ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, three studies examined monosaccharides in breast milk. Two studies examined glucose, with Choi et alfound that GDM reduced glucose concentrations in colostrum [38], while Kaushik et al stated that GDM did not affect glucose in mature milk [12]. Additionally, using metabolomics techniques, Wu et al found that GDM reduced the concentrations of iditol, galactitol, and sorbitol in breast milk [35].…”
Section: Carbohydratesmentioning
confidence: 99%
“…Of the three studies that examined colostrum and mature milk, one indicated that GDM increased insulin concentrations [27] and the other two suggested no effect [16,26]. In contrast, Choi et al suggested that it would decrease concentrations in mature milk [38].In addition, two studies have examined IGF-1 levels in breast milk and both indicated that GDM had no effect on it [33,34]. Three studies tested ghrelin concentrations in the milk.…”
Section: Hormonesmentioning
confidence: 99%
See 1 more Smart Citation